Dinamika cognitive load dan self-correction siswa dalam menyelesaikan masalah geometri pada subjek tunggal - Fitriana Fitriana (IKIP Siliwangi, 2026)
This study explores the high cognitive load in non-routine geometry that triggers epistemological barriers for students. Its novelty lies in the analysis of the self-correction mechanism as a cognitive bridge. The purpose of the study is to analyze the role of metacognitive awareness in guiding strategy changes when subjects experience deadlock. The research method used descriptive qualitative with a single case study design on one student. Data were collected through the Think Aloud Protocol and task-based interviews, validated by triangulation of methods, and analyzed inductively. Findings on this subject show that metacognitive evaluation is a crucial turning point for detecting strategy incoherence. As preliminary findings, this study describes the function of metacognition as a controller that transforms errors into a productive knowledge construction process. These results are specific to the cognitive characteristics of the research subjects and cannot be generalized broadly. However, this study provides an important perspective for the development of reflective scaffolding in geometry learning to help students manage cognitive load independently.